Short-term effects of smoking cessation: benefit or penalty? - Young, R. C. (National Medical Association, 1989)
Eight of ten cigarette smokers successful in a smoking cessation group therapy program were examined, initially, and at six and 12 months postcessation. Examination included completion of a respiratory questionnaire and selective pulmonary function testing that included maximum expiratory flow volume curves, slope of phase 3 alveolar plateau, and closing volume. Two symptomatic subjects became symptom-free within six months postcessation. Results indicate a mean weight gain of 4.1 kg within 12 months (P less than 0.01), deterioration in mean forced expiratory volume in one second as percent of forced vital capacity (P less than 0.05), and deterioration in mean forced expiratory volume in three seconds as percent of forced vital capacity postcessation (P less than 0.05). Other tests derived from the maximum expiratory flow-volume curve, slope of phase 3, or closing volume showed no change. These results may be explained by a number of factors and may have implications for future studies.